Effectiveness of photodynamic therapy in Bowen's disease: a retrospective observational study in 423 lesions. (10th March 2017) - Zaar, O.; Fougleberg, J.; Hermansson, A.; Gillstedt, M.; Wennberg‐Larkö, A.‐M.; Paoli, J.
Abstract: Background: Photodynamic therapy (PDT) is a well‐known technique that is often used for treating superficial precancerous and cancerous skin lesions. However, only a handful of studies, with a relatively small number of treated lesions, have been carried out on the effectiveness of PDT for Bowen's disease (BD). Objectives: This study aimed to assess the effectiveness and recurrence risk of PDT in the treatment of BD. The secondary objectives were to determine what factors affected the response rates and the cosmetic result of the treatment. Method: In this retrospective observational study, the electronic patient charts at Sahlgrenska University Hospital (SUH) in Gothenburg, Sweden, were searched to find all patients diagnosed with BD who were treated with PDT between 1 January 2002 and 31 December 2014. Data were collected regarding clinical response at the first follow‐up visit, recurrences during later follow‐up visits and other relevant patient and tumour characteristics. Results: In total, 423 BD lesions in 335 patients were included in the study. The mean FU duration was 11.2 months (range 0.2–151 months). The complete response rate at the first FU visit was 77.5% for all BD lesions. During later FU visits, another 60 recurrences were observed, which resulted in a recurrence rate of 18.3%. Thus, the overall clearance rate after FU was 63.4% for all BD lesions. Significant risk factors for unsuccessful treatment in this study were large lesion size (>2 cm) and a single PDT session. Conclusion: This study shows that PDT is a relatively effective treatment modality for BD.